2020
DOI: 10.3233/mnm-190382
|View full text |Cite
|
Sign up to set email alerts
|

Impact of migration on dietary patterns and adherence to the Mediterranean diet among Northern Moroccan migrant adolescents in Madrid (Spain)

Abstract: BACKGROUND: Few studies have compared the diets of minor migrants with similar ethnic groups in the country of origin. Although Moroccans form the largest foreign population group in Spain, there is limited information on their dietary changes and the effects on nutritional status. AIM: To determine whether migration has caused changes in adherence to the Mediterranean diet (MD) in a sample of Moroccan adolescents living in Madrid (Spain) compared with their peers in northern Morocco (Al Hoceima). METHODS: A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…These outcomes may be explained by the reasons put forth by Galán-López et al [ 51 ] and Rosi et al [ 28 ], who explain that students older than eleven years start to take control over their own diet, in this way increasing their negative dietary patterns. In addition, El Mokhatari et al [ 52 ] concluded that worse dietary outcomes are obtained at the educational stage corresponding to compulsory secondary education, with this stage also coinciding with the start of adolescence.…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes may be explained by the reasons put forth by Galán-López et al [ 51 ] and Rosi et al [ 28 ], who explain that students older than eleven years start to take control over their own diet, in this way increasing their negative dietary patterns. In addition, El Mokhatari et al [ 52 ] concluded that worse dietary outcomes are obtained at the educational stage corresponding to compulsory secondary education, with this stage also coinciding with the start of adolescence.…”
Section: Discussionmentioning
confidence: 99%